The Loss of HIF1α Leads to Increased Susceptibility to Cadmium-Chloride-Induced Toxicity in Mouse Embryonic Fibroblasts - Vengellur, Ajith (Hindawi Publishing Corporation, 2011)
Wild-type and HIF1α −/− MEF cells were used to determine the role of HIF1α in cadmium-induced toxicity. Cadmium treatment did not affect HIF1-mediated transcription but led to caspase activation and apoptotic cell death in wild-type and HIF1α −/− cells. Cadmium-induced cell death, however, was significantly higher in HIF1α −/− cells as compared to their wild-type counterparts. Increased cell death in the HIF1α −/− cells was correlated with lower metallothionein protein, elevated levels of reactive oxygen species, and decreased superoxide dismutase enzyme activity. The total and oxidized glutathione levels, and, correspondingly, lipid peroxidation levels were elevated in the null cells compared to wild-type cells, indicating increased antioxidant demand and greater oxidative stress. Overall, the results suggest that basal levels of HIF1α play a protective role against cadmium-induced cytotoxicity in mouse embryonic fibroblasts by maintaining metallothionein and antioxidant activity levels.